2001
DOI: 10.1021/jp0121466
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Study of the Structure and Polarizability of Sulfur Clusters, Sn (n = 2−12)

Abstract: The structure and the dipole polarizabilities of S n clusters (n ) 2-12) have been calculated using density functional theory within the B3LYP approximation and conventional ab initio Hartree-Fock (HF) and coupledcluster with single and double and perturbative triple excitations (CCSD(T)) methods. The results show that the binding energy per atom increases with the size of the cluster and reaches the asymptotic limit for a relatively small n value. There is an excellent agreement between B3LYP and CCSD(T) data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
50
1
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 82 publications
14
50
1
1
Order By: Relevance
“…This suggests that the even-numbered selenium clusters are relatively more stable than the neighbouring oddnumbered ones. Specifically, among the cyclic clusters, Se 6 and Se 8 display the highest positive D 2 E values, in agreement with the data previously reported by Li et al [44] for the Se n (n = 2-7) clusters and with the S n (n = 2-12) clusters [81]. Note that, the electron correlation effects on the D 2 E values are noteworthy for the smallest clusters, whereas they are minimal for the largest ones (Se n , n C 6).…”
Section: Structures and Energeticssupporting
confidence: 92%
See 2 more Smart Citations
“…This suggests that the even-numbered selenium clusters are relatively more stable than the neighbouring oddnumbered ones. Specifically, among the cyclic clusters, Se 6 and Se 8 display the highest positive D 2 E values, in agreement with the data previously reported by Li et al [44] for the Se n (n = 2-7) clusters and with the S n (n = 2-12) clusters [81]. Note that, the electron correlation effects on the D 2 E values are noteworthy for the smallest clusters, whereas they are minimal for the largest ones (Se n , n C 6).…”
Section: Structures and Energeticssupporting
confidence: 92%
“…? is estimated to be 0.44 eV smaller (-16 %) than that for the sulphur clusters, previously determined at the same level of calculation [81].…”
Section: Structures and Energeticscontrasting
confidence: 49%
See 1 more Smart Citation
“…It is found that the binding energy per sulfur atom increases with the size of the cluster and reaches the asymptotic limit at about S 6 with S 2 , S 6 and S 8 particularly stable. Of interest in the context of field effects is the finding that the polarisability increases with the cluster size correlating linearly with the molecular volume [26]. The propensity of sulfur to catenation leads to over 20 crystalline allotropes all of which are composed of homocyclic rings with as much as 20 atoms.…”
Section: Polymerization Of Sulfur In High Electric Fieldsmentioning
confidence: 99%
“…Moreover, Millefiori et al have considered D 2d , D 2h , C 2v , and C 2h symmetry of the neutral S 4 by using DFT within the B3LYP approximation. 22 Their results suggest that C 2v , D 2d , and C 2h are minima at B3LYP/cc-pVDZ potential energy surface but that the rectangular D 2h is a transition state and the planar C 2v form to be the ground state. The D 2h is higher in energy by 2.11 kcal mol…”
Section: ç Neutral S 4 Moleculementioning
confidence: 99%